RENEGOTIATION ACCOUNTING. - Larimore, Theodore R. (The Accounting Review, 1955)
Renegotiation is not a taxing device. It is, rather, a measure to induce closer pricing, and prevent the retention of excessive profits. The Renegotiation Board was created by the U.S. Renegotiation Act of 1951 as an independent agency, and was organized on October 3, 1951. The Renegotiation Board decided at the outset that it would be guided by two common sense considerations. In the first place, the board determined that its rules and procedures would be kept as simple as the nature of its responsibilities permitted and, in the second place, that all businesses affected by the act would be treated fairly and in like manner. The board also decided that, to a greater extent than had been true in the past, business would be informed at all times of the actual procedures and techniques employed in the renegotiation of cases. The general accounting steps in processing cases in the Regional Board, and the problems of renegotiation are discussed in the article. The basic accounting problems are associated with the segregation of sales and the allocation of costs and expenses between renegotiable and non-renegotiable business.